Equilibrium and Kinetic Studies on the Adsorption of Methylene Blue from Aqueous Solution onto Activated Carbon Prepared from Murraya koenigii (Curry Tree) Stems - Suresh, S.; Wilfred Sugumar, R.; Maiyalagan, T. (Asian Journal of Chemistry, 2011)
In the present study, activated carbon is prepared from Murraya koenigii Stems (MKST) and used for the adsorption of methylene blue from aqueous solution. The nitrogen adsorption isotherms were used to characterize the pore properties of the activated carbon including the BET surface area, pore volume and pore diameter. The specific surface area of the prepared carbon is 508 m2/g. Batch mode experiments were conducted to study the effect of adsorbent dosage on the adsorption of methylene blue. The equilibrium data fits well with Langmuir model with monolayer adsorption capacity of 123.46 mg/g. The adsorption kinetics was studied using pseudo-first order and pseudo-second order models. The rate of adsorption was found to conform to pseudo-second order kinetics with a good correlation. The results show that methylene blue interacts strongly with the prepared activated carbon and hence the adsorbent is good for the removal of methylene blue from aqueous solution.